2020
DOI: 10.1021/acs.jpclett.0c02846
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Based Potential Vaccine Candidate for Humoral and Cell-Mediated Immunity to Combat Severe Acute Respiratory Syndrome Coronavirus 2 Pandemic

Abstract: The emergence of severe acute respiratory syndrome from novel Coronavirus (SARS-CoV-2) has put an immense pressure worldwide where vaccination is believed to be an efficient way for developing hard immunity. Herein, we employ immunoinformatic tools to identify B-cell, T-cell epitopes associated with the spike protein of SARS-CoV-2, which is important for genome release. The results showed that the highly immunogenic epitopes located at the stalk part are mostly conserved compared to the receptor binding domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…It is pertinent to note that the predicted continuous B-cell epitopes reported in this study have been previously identified using similar computational tools, and some of the predicted epitopes have now been experimentally validated (Tables 2 – 9 ). Similar findings presented in this work have been reported previously [ 27 38 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It is pertinent to note that the predicted continuous B-cell epitopes reported in this study have been previously identified using similar computational tools, and some of the predicted epitopes have now been experimentally validated (Tables 2 – 9 ). Similar findings presented in this work have been reported previously [ 27 38 ].…”
Section: Resultssupporting
confidence: 93%
“…In this study, we predicted B- and T-cell epitopes using multiple prediction servers by leveraging existing immunological knowledge and the genetic closeness of SARS-CoV-2 with SARS-CoV [ 4 6 ]. Previous studies have identified epitopes mainly on the S protein of SARS-CoV-2 ( Table 1 ) using a limited number of prediction servers [ 27 38 ]. Using well-established prediction tools, we identified potential B- and T-cell epitopes in the structural proteins (S, E, M, and N) of SARS-CoV-2 ( Fig 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…El Hassab et al perform fragment based drug design and link together generated fragments binding to RdRp ( El Hassab et al, 2020 ). Potential vaccine candidates derived from B-cell and T-cell epitopes from the spike protein have their binding stability assessed through MD simulation ( Das and Chakraborty, 2020 ).…”
Section: Applications To Drug Discoverymentioning
confidence: 99%